Stateliest measures : Tennyson and the literature of Greece and Rome - Markley, A. A. (Toronto ; Buffalo : University of Toronto Press, 2004)
"Stateliest Measures, the first full-length study of Tennyson's thematic and metrical uses of classical material, examines the profoundly important role that his classical background played as he fashioned himself into a poet in the 1820s and 1830s, and as he defined himself as poet laureate as of 1850." "A. A. Markley examines Tennyson's objectives in developing the classical dramatic monologue, which, together with In Memoriam and his experiments with classical meters, indicate the degree to which he patterned himself after the Roman poet Virgil in attempting to provide modern Britain with a literature worthy of a new and rapidly expanding world empire. Stateliest Measures demonstrates that Tennyson's engagement with the long-running and complex nineteenth-century debates concerning Hellenism, Imperialism, and modern British culture was much more profound than previously recognized."--Jacket
Introduction : the English Virgil -- Tennyson's classicism in context : the Victorians and the ancient world -- The building blocks of song : constructing the classical dramatic monologue -- Et in Arcadia : transcending the classical elegy in In memoriam -- Classical prosody and the 'Ocean roll of rhythm' -- The trilogy on death : 'Ulysses, ' 'Tithonus, ' and 'Tiresias' -- Old tales for a new day : Lucretius, Demeter, and Œnone's return.
Includes bibliographical references (pages 197-221) and index.
Some text in Latin.
JSTOR
Keywords: Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Knowledge -- Literature; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Knowledge -- Greece; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Knowledge -- Rome; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Critique et interprétation.; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892; Tennyson, Alfred; Tennyson, Alfred; Classicism -- England -- History -- 19th century; Classical literature -- Appreciation -- England; English poetry -- Classical influences; Mythology, Classical, in literature; Greece -- In literature; Rome -- In literature; Poésie anglaise -- Influence ancienne; Classicisme -- Angleterre -- Histoire -- 19e siècle.; Mythologie ancienne dans la littérature.; POETRY -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Classical literature -- Appreciation; Classicism; English poetry -- Classical influences; Literature; Mythology, Classical, in literature; England; Greece; Rome (Empire); Literatur; Klassische Philologie; Griechisch; Latein; 1800-1899; Electronic books; History; Literature